Evidence-based practice. Psychometric properties of a questionnaire its measurement (2014)
Objective: The questionnaire developed in the U.S by Jette et al. is used as a screening tool to estimate the attitudes, beliefs, knowledge and behaviors toward evidence-based practice (EBP). This instrument was adapted and validated in the Spanish language by Guerra et al., but lacking validity studies in the Hispanic population. This research has aimed to estimate the psychometric properties as a way to obtain evidence on the validity of the instruments for the use proposed. Method: The sample was made up of 1,064 Physiotherapists in Colombia who completed the on-line version of the questionnaire. Its reliability and reproducibility were estimated with Cronbach's alpha procedure, the test-retest with Lin' correlation coefficient and Cohen's kappa index, respectively. An exploratory factor analysis was used to analyze the factorial structure. Results: The questionnaire has shown global high internal consistency, moderate temporal stability, acceptable reproducibility, and construct validity appropriate. Exploratory factorial analysis identified two factors that account for 37.953% of the variance. Conclusions: The results obtained in this study support the use of this questionnaire for this type of sample from the viewpoint of reliability and factor structure. However, further studies are needed to provide evidence of validity based on the relationship with other variables to determine its usefulness as a questionnaire to evaluate the EBP. © 2013 Asociación Española de Fisioterapeutas.